THE EFFECT OF WORKING CAPITAL TURNOVER, CAPITAL STRUCTURE AND COMPANY SCALE ON PROFITABILITY IN AUTOMOTIVE COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE - Yayu Rakkang, Yayu Rakkang; Mariam Makmur, Mariam Makmur; Sri Wirdana, Sri Wirdana (Jurnal Manajemen Dan Bisnis, 2023)
The Impact of Internal Auditors' Work Experience and the Use of Accounting Information Systems on Fraud Detection at PT. Bank SulselBar Makassar's Head Office (supervised by Baso R and Surianto) This study aims to ascertain whether internal auditors' work experience and the use of accounting information systems impact fraud detection at the head office of PT Bank SulselBar Makassar. Primary data are collected using saturated sampling methods using surveys. The population consists of all 37 Bank SulselBar Makassar Head Office employees, and the sample size is 35 respondents. The validity and reliability of the questionnaire's results have been examined, and the traditional premises of normalcy, multicollinearity, and heteroscedasticity have also been scrutinized strategies for conducting simple regression analyses. The findings of this study suggest that the presented hypothesis is correct because the hypothesis testing yielded significant and favorable outcomes. This indicates that using accounting information systems and the internal auditors' professional experience positively and significantly impact fraud detection.